Changes in Winter Temperature Extremes From Future Arctic Sea‐Ice Loss and Ocean Warming. Issue 3 (1st February 2023) - Lo, Y. T. Eunice; Mitchell, Dann M.; Watson, Peter A. G.; Screen, James A.
Abstract: Observed rapid Arctic warming and sea‐ice loss are likely to continue in the future, unless and after greenhouse gas emissions are reduced to net‐zero. Here, we examine the possible effects of future sea‐ice loss at 2°C global warming above pre‐industrial levels on winter temperature extremes across the Northern Hemisphere, using coordinated experiments from the Polar Amplification Model Intercomparison Project. 1‐in‐20‐year cold extremes are simulated to become less severe at high‐ and mid‐latitudes in response to Arctic sea‐ice loss. 1‐in‐20‐year winter warm extremes become warmer at northern high latitudes due to sea‐ice loss, but warm by less than cold extremes. We compare the response to sea‐ice loss to that from global sea surface temperature (SST) change also at 2°C global warming. SST change causes less severe cold extremes and more severe warm extremes globally. Except northern high latitudes, the response to SST change is of larger magnitude than that to Arctic sea‐ice loss. Plain Language Summary: The Arctic and neighboring regions have rapidly warmed in recent decades and the sea ice has reduced. These changes will likely continue in future, unless greenhouse gas emissions from human activities are reduced to net‐zero. Ongoing sea‐ice loss can affect weather and climate across the Northern Hemisphere. We use climate models to study how extremely cold and hot temperatures in winter may change because of Arctic sea‐ice loss. In a future world that is, on average, 2°C warmer than pre‐industrial times, cold extremes will become less severe at high‐ and mid‐latitudes because of Arctic sea‐ice loss. Winter hot extremes also get warmer, but over fewer regions and not by as much as cold extremes. In the real world, changes in sea ice happen alongside changes in ocean temperatures. So, we also looked at the effect of ocean temperature changes in a 2°C warmer world on winter temperature extremes. Ocean warming will lead to warmer cold and hot extremes in the Northern Hemisphere. The effect from ocean warming is larger than that from Arctic sea‐ice loss, meaning that even in the few places where sea‐ice loss might cause cooling, it will be overwhelmed by warming due to the ocean temperature changes. Key Points: Less severe winter cold extremes in northern mid‐ and high‐latitudes in response to future Arctic sea‐ice loss Winter hot extremes increase in severity over high latitudes due to future Arctic sea‐ice loss, but warm less than cold extremes In a majority of the latitudes, both cold and hot extremes warm more in response to future global sea surface temperature change than due to sea‐ice loss